Transfer of Receivables to Third Parties through Cessie - I Made Pria Dharsana; Indrasari Kresnadjaja (Law Doctoral Community Service Journal, 2023)
Cessie is a transfer of rights over intangible movable goods which are usually in the form of receivables on behalf of third parties, where a person sells his claim rights to another person. In activities at the cessie travel bank, it starts with the working capital needs of a company due to a breakdown in accounts receivable and receipts. So, to bridge the gap, a factoring business emerged in return for commission fees based on the cessie. The purpose of this study is to determine the form of transfer of receivables. This type of study uses a normative juridical research method that is analyzed descriptively. The results of this study can be concluded that Cessie is a term coined by doctrine, to refer to the act of submitting invoices on behalf of, as stipulated by Article 613 BW (burgelijk wetbook) which submission is carried out by making a deed. The deed of submission of invoices on behalf of is called a cessie deed.